Access through road in Pahing Hamlet, Sukadana Village, Kuningan Regency as a means of improving the community's economy - Saefullah, Aep; Radjawane, Louise Elizabeth; Sutrisno, Eko; Santoso, Aprih; Kuraesin, Arlis Dewi (Goodwood Publishing, 2023)
Purpose: This study aims to investigate and examine the effects of improved road access on the economy of residents of Pahing Hamlet, Sukadana Village, and Kuningan Regency. Research methodology: The research method used was qualitative, involving data collection through field observations, in-depth interviews, and documentation . Results: The findings indicate that improved access to the through-road in Sukadana Village significantly enhanced the economic condition of the Pahing Hamlet community. Enhanced road access enables farmers and local traders to reach markets and potential customers more easily, thereby improving accessibility and mobility of goods. This positively affects local income, business growth, and community economic empowerment. Limitations: Although improved road access yields tangible benefits, some limitations of this study should be acknowledged. First, this research is limited to Pahing Hamlet in Sukadana Village; thus, generalizing the results should be approached with caution. Second, the study does not thoroughly examine other factors such as supporting infrastructure and government policies, which also affect community economic improvement. Contribution: This study contributes to a better understanding of the potential advantages of village economic empowerment in rural development and identifies strategies that can be implemented in other rural areas. It recommends that governments and development organizations prioritize supporting village economic empowerment initiatives and collaborate closely with local communities to overcome the challenges and obstacles to implementation.